Attentional Bias, Alcohol Craving, and Anxiety Implications of the Virtual Reality Cue-Exposure Therapy in Severe Alcohol Use Disorder: A Case Report - Ghiţă, Alexandra; Hernández-Serrano, Olga; Fernández-Ruiz, Jolanda; Moreno, Manuel; Monras, Miquel; Ortega, Lluisa; Mondon, Silvia; Teixidor, Lidia; Gual, Antoni; Gacto-Sanchez, Mariano; Porras-García, Bruno; Ferrer-García, Marta; et al. (Frontiers in Psychology, 2021)
There is a direct relationship between alcohol-related stimuli and attentional bias (AB) toward alcohol-related content and elicitation of craving and anxiety. AB, alcohol craving and anxiety have important implications in the development and maintenance of alcohol use disorder (AUD). This study aims to test the efficacy of a Virtual Reality Cue-Exposure Therapy (VR-CET) in a patient diagnosed with severe AUD, who made several failed attempts to cease alcohol drinking. A 49-year-old male participated in this study after providing written informed consent. The protocol consisted of six VR-CET booster sessions and two assessment sessions (pre and post VR-CET) over the course of five weeks. The initial assessment session (pre VR-CET) consisted of collecting clinical data and the administration of multiple tasks assessing alcohol craving, anxiety and AB. In addition, momentary cue-induced craving and anxiety levels were explored during a VR assessment task and the Multidimensional Alcohol Craving Scale and State-Trait Anxiety Inventory respectively. AB toward alcohol-related content was explored with the Alcohol Stroop Task and a Visual Attention Task (VAT) using eye-tracking technology. VR-CET booster sessions consisted of exposure to preferred alcoholic beverages and alcohol-related contexts, using the ‘ALCO-VR’ software. Throughout the six VR-CET sessions, momentary anxiety and alcohol craving levels were recorded during exposure to VR alcohol-related cues and contexts. In the final assessment session (post VR-CET), data of craving, anxiety and AB were recorded using the same instruments as in the first assessment session. After the six VR-CET booster sessions, cue-induced momentary anxiety and craving levels were reduced to minimum scores. Pre and post assessment sessions indicated falls on the scores of all instruments assessing alcohol craving, anxiety and AB. This case report, part of a larger project aiming to test the efficacy of the VR-CET in patients diagnosed with severe AUD, demonstrates the efficacy of the VR-CET booster sessions. In the post-treatment measurements, a variety of instruments showed a change in the AB pattern and an improvement in craving and anxiety responses. As a result of desensitization, virtual exposure gradually reduced the responses to significant alcohol-related cues and contexts. The implications for AB, anxiety and craving are discussed.